Encenação e ubiquidade em discursos no Twitter : procedimentos de análise - Boaventura, Luis Henrique (2017)
This work deals with the staging of the language act in verbal interactions in the social network Twitter. The general objective is to analyze and discuss the functioning of the language act in the era of hypermobility. The theoretical framework is based on three bases: the ethical act and the aesthetic valuation in Mikhail Bakhtin (1997, 2012), the ubiquitous communication in Lucia Santaella (2010, 2013a) and the Semiolinguistic Theory in Patrick Charaudeau (2010a,2010b). The thesis is that the communication in the RSI Twitter, when negotiated around a highly polarizing matter, such as politics, tends to sign contracts exclusively between individuals who share the same pole of argument, aiming at a mutual legitimation and maintaining the construction of meaning trapped inside an autophagic circuit that turns on its axis without leaving the place. This communication is ubiquitous and its participants are placed ambivalently about a physical social space and a virtual social space. This condition, of dual existence, gives rise to the ubiquitous enunciator (EUu), which enacts the language act through a link between two simultaneous social presences: its virtual projection and its physical correlative. The study is based on the exploratorydescriptive, bibliographical research with a qualitative approach in relation to the Semiolinguistic Theory, the philosophy of the responsible act and the ubiquitous communication. The corpus is composed of two tweets in reaction to the announcement of the death of former First Lady Dona Marisa Letícia, on February 3, 2017. The work reveals that US antagonizes its apparent recipient, the OP enunciator (original poster), whom offers its response, and enacts the act of language to a TUu-recipient institution (real recipient) composed of users, ubiquitous subjects, who share their side of the polarizing spectrum, negotiating with this TUu the counterpart of connivance that validates their speech and reinforces his consciousness identity in a double movement: how much more similar to TUu; the more different from OP. Key words: Language act. Ubiquitous communication. Ethical act. Identity. Twitter.